Reports from health professionals in contact with the subject of integrative practices and spirituality in health: Experiences, reflections and science (Research, Society and Development, 2021)
Integrative and Complementary Practices in Health (PICS) have constituted a fertile field to ensure the promotion of health and quality of life. As a result, discussions about spirituality have gained social relevance. This article aimed to reflect on the experiences of health professionals in the course of a discipline on PICS, integrating them with spirituality. This was a descriptive study of reports from these professionals, after completing the course "Special Topics in Health Research III - Integrative Practices and Spirituality in Health: Experiences, Reflections and Science", offered by the Programa de Pós-Graduação em Saúde e Sociedade (PPGSS) da Universidade do Estado do Rio Grande do Norte (UERN). The results evoked the need to expand the curriculum in undergraduate health courses on PICS and spirituality. The contact with disciplines that thematize the PICS, aspects of spirituality, as well as the relationship with integral health, proved to be significant, as this study aimed to present through the discussion of reports.